(untitled) (KULT_online, 2015)
Erdmute Alber, Professor for Social Anthropology at the University Bayreuth, lived and conducted research in West Africa for over 20 years. The result is the monograph Soziale Elternschaft im Wandel, an extensive ethnographical study on the West African Baatombu tribe. The study’s focus is the Baatombu’s practice of social parentage and is remarkable for two main reasons: First, Alber grants the reader an intensive look into the lives of the Baatombu over (the past) 20 years. Secondly, and as a result, observing (the Baatombu version of collective) parentage creates a deeper understanding of this concepts cultural relativity.